Is the New Law on Family Violance a Failure? - Ristivojević, Branislav (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
In this article author deals with the problem of a sudden increase of a number of women killed in family violence in Srbia. What was reported, but somehow fel out of a sight of all observers and commentators is that approximately 2/3 of perpetrators of these femicids commited suicide after initial deed. Since there are no significant anomalies in serbian society besides introduction of a new Law on prevention of a family violence, the reason for this abrupt explosion of this  femicid/suicid combination must sit within it. Author argues that urgent measures, as the Law calls they, which are imposed on a possible perpetrator of a family violence, have in fact all material characteristics of a punishments, and these would be very heavy since one is forbidden from seeing his family or living within his apartment, but they are not pronounced in a court of law after a due criminal procedure. Moreover, individuals which are imposed to these urgent measures did not do anything bad since they are called by the Law the possible perpetrators. That means that they did not do anything but might, in the future, perpetrate some act of a family violance. So they are some sort of the quasi-perpetrators. Hence, a short conversation with a simple police officer leads to the effect which would normally first demand an act to have been done and then it would take a month of a contradictory presentation of a evidence before a competent court. Finally, there would be right to a appeal. It is no wonder that urgent measures are in fact seen as extremlly illegitimate and unfounded, and as a form of quasi-punishments, they provoked this deadly reacton. Knowing that individuals who are prone to suicide are in such a despair, that they see the only exit from their living problems in complete nullity, we can only imagine in what an extreme scope of hopelessness they are brought, since they opted for a total nonexistence.  In a sum, with the urgent measures lawgiver created functional equivalent of a harshest criminal penalties but whitout heavy burden of a criminal procedure. By this he created a mongrel with deadly consequences. Penal repression which is seen as a extremely illegitimate leads to extreme resistance and refusal whose final consequence could be deterioration and aggravation of a societal phenomenon which it allegedly tried to solve.